Assessing Agro-Climatic Indices, Productivity and Profitability of Late Planted Chickpea through Climate Change Adaptation Measures in Madi, Chitwan - Amagain, L. P.; Dhakal, U. (Journal of Agriculture and Environment, 2019)
Available with full text.